Central Roles and Regulatory Mechanisms of Dual-Specificity MAPK Phosphatases in Developmental and Stress Signaling - Jiang, Lingyan; Chen, Yinhua; Luo, Lijuan; Peck, Scott C. (Frontiers in Plant Science, 2018)
Mitogen-Activated Protein Kinase (MAPK) cascades are conserved signaling modules that integrate multiple signaling pathways. One level of control on the activity of MAPKs is through their negative regulators, MAPK phosphatases (MKPs). Therefore, MKPs also play an integrative role for plants responding to diverse environmental stimulus; but the mechanism(s) by which these phosphatases contribute to specific signals remains largely unknown. In this review, we summarize recent advances in characterizing the biological functions of a sub-class of MKPs, dual-specificity phosphatases (DSPs), ranging from controlling plant growth and development to modulating stress adaptation. We also discuss putative regulatory mechanisms of DSP-type MKPs, which plants may use to control the correct level of responses at the right place and time. We highlight insights into potential regulation of cross-talk between different signaling pathways, facilitating the development of strategies for targeting such cross-talk and to help improve plant resistance against adverse environmental conditions without affecting the growth and development.